2011
DOI: 10.1097/jom.0b013e31820a40a3
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cancer Risk and Occupational Exposure to Polycyclic Aromatic Hydrocarbons and Plastics

Abstract: Objective-To investigate whether occupational exposure to polycyclic aromatic hydrocarbons and certain plastic monomers increased renal cell carcinomas (RCC) risk.Methods-Unconditional logistic regression was used to calculate RCC risk in relation to exposure.Results-No association between RCC risk and having ever been occupationally exposed to any polycyclic aromatic hydrocarbons or plastics was observed. Duration of exposure and average exposure also showed no association with risk. Suggestive positive assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Animal studies indicated that ACN possesses mutagenic [12], carcinogenic [13], immunotoxic [14], embryotoxic [15] and neurotoxic properties [16]. Clinical studies indicated increased risk of lung cancer, brain cancer and renal cell carcinoma in some exposure categories 17,18]. …”
Section: Bacgroundmentioning
confidence: 99%
“…Animal studies indicated that ACN possesses mutagenic [12], carcinogenic [13], immunotoxic [14], embryotoxic [15] and neurotoxic properties [16]. Clinical studies indicated increased risk of lung cancer, brain cancer and renal cell carcinoma in some exposure categories 17,18]. …”
Section: Bacgroundmentioning
confidence: 99%
“…PAHs can bioaccumulate through the food chain because of its resistance to degradation (Mumtaz et al, 1996). Most studies studying the adverse health effects of PAHs have focused on increasing risks of chronic diseases such as cardiovascular diseases (CVD) and a variety of cancers (Burstyn et al, 2005;Cai et al, 2012;Gammon et al, 2002Gammon et al, , 2004Grant, 2009;Karami et al, 2011;Rundle et al, 2000;Sagiv et al, 2009;Xia et al, 2013;Xu et al, 2010). Recently, several studies have suggested an association between ambient air pollution with type 2 diabetes (T2DM) and the effects to potentially induce insulin resistance (Andersen et al, 2012;Brook et al, 2008;Coogan et al, 2012;Kramer et al, 2010;Pearson et al, 2010;Raaschou-Nielsen et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Estimates from case-control studies ranged from 1.6 to 9.3-fold increased risk of kidney cancer associated with exposure of PAHs working with iron steel, coke, coal tar pitch and asphalt, although these studies relied on selfreported exposure. 5152 …”
Section: Discussionmentioning
confidence: 99%